Protective effects of silibinin on LPS-induced inflammation in human periodontal ligament cells - Meng, Di; Wang, Yuling; Liu, Tongjun (Frontiers in Chemistry, 2022)
Periodontitis is clinically one of chronic nonspecific inflammation, leading to the damage to teeth and surrounding mouth. Although many researches on periodontitis have been conducted, but the therapy of natural products is still really rare. Silibinin has been proved to exist anti-inflammatory and antioxidant activities. But the effects of silibinin on LPS-induced inflammation in PDLs are not discovered. In this investigation, PDLs were treated with silibinin (10, 20, 40μM) in the presence of LPS. The results showed that silibinin treatment reduced levels of NO, PGE2, IL-6, TNF-α, MMP-1, and MMP-3, and enhanced the activities of SOD and GSH. Moreover, silibinin treatment could downregulated level of RANKL and upregulated levels of OPG and ALP. In summary, silibinin protected PDLs against LPS-induced inflammation, oxidative stress, and osteogenic differentiation capacity.